Implementasi Pendidikan Karakter Berbasis Pesantren dalam Meningkatkan Kualitas Kepribadian Peserta Didik (Studi Kasus di MINU KH. Mukmin, Sidoarjo) - Sholehuddin Sholehuddin; Achmad Achmad; Abd. Waras; Khanif Amanullah (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
This study aims to analyze the implementation of Islamic Boarding School-Based Character Education (PKBP) which focuses on improving the personality qualities of students at MINU KH. Mukmin Sidoarjo. The study method used is descriptive qualitative by collecting data through participatory observation, in-depth interviews, and document techniques. The collected data were then analyzed using the theory from Milles and Huberman, which includes descriptive narrative, data reduction, data presentation, and conclusion. Data validity was checked through credibility, transferability, dependability, and confirmability tests. The results showed that the implementation of PKBP at MINU KH. Mukmin Sidoarjo involves four aspects: teaching and learning activities, extracurricular activities, Islamic boarding school religious activities implemented in schools, and supporting activities. To improve the quality of personality, focus is given to inculcating the values of religious character, honesty, discipline, tolerance, independence, hard work, curiosity, national spirit or nationalism, communication, fondness of reading, environmental and social care, and responsibility. The PKBP strengthening program is carried out in three ways, namely extracurricular, co-curricular and extracurricular programs.